Valproate-Induced Lupus Erythematosus - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
A mentally retarded 30-year-old woman with partial trisomy of chromosome 9, suffering from epilepsy since age 11 months, developed systemic lupus erythematosus after one year of treatment with valproate (VPA) and ethosuximide (ESM) at the Clinica Neurologica, Universita di Roma Tor Vergata, Italy.